Resistência a mudança no uso de ferramentas de gestão - Sousa, Cirilo Nascimento de (2018)
The general ranking of this article is a change in the tools of employment of companies. The research was carried out through the data collection using the online questionnaire with objective questions and recorded interview. The research was structured by the exploratory study, since it sought to know the collaborator within the work environment with safety to the changes. (GIL, 2008). The result is a research on what is a problem in the power of attention levels, although it is positive, however, the presence of passive resistance is noticed.